One-stage repair for combined fistulas: myth or reality? (2007)
Objective: The repair of combined vesico-vaginal fistulas (VVFs) and recto-vaginal fistulas (RVFs) is challenging to both surgeon and patient. The multistage approach involves at least 3 surgical sessions, all associated with morbidity and sometimes with a colostomy procedure as well. The outcomes of the 1-stage approach were examined. Methods: Twenty patients aged between 16 and 38 years were recruited for a multicenter study conducted from March 2005 to August 2006. Prolonged obstructed labor was the cause of all fistulas. The VVFs were mainly midvaginal (60%), juxtaurethral (25%), and juxtacervical (15%). The RVFs measured between 1 and 3 cm, they were low in 70% of cases, and 1 was associated with fourth-degree perineal tear. Bowel preparation was performed in all patients prior to surgery. No patient underwent temporary colostomy. Results: Both VVFs and VVFs were successfully closed in all patients, as evidenced by thecontinence dye test. Conclusion: The combined repair relieves economic constraints and emotional challenges, and it accelerates restoration to health and social reintegration for women affected with both VVFs and RVFs